Acute effect of strength training on pain in women with fibromyalgia: A brief report - De Azevedo Klumb Steffens R.* (2021)
© 2021-IOS Press. All rights reserved.OBJECTIVE: The aim was to analyze the effect of one session and three sessions of strength training (ST) on pain in women with fibromyalgia (FM). METHOD: Twenty-three women with FM performed three sessions of ST for a week. Each training session worked the main muscle groups and lasted 60 min. Three sets of 12 repetitions were performed with 1 min intervals in between. The load was increased based on the perception of subjective effort of each patient. Pain intensity was evaluated immediately after the first and third sessions using a Fischer digital algometer. RESULTS: After the first ST session, pain reduction was observed. No significant differences were found in pain thresholds on the baseline versus the third session. The analysis of MBI demonstrated that the ST does not worsen patients' pain, indicating a 52.2% trivial effect and a 39.1% beneficial effect. CONCLUSION: Our results suggest that there is no harmful effect on the pain of women with FM after an acute session of ST. We emphasize that despite the promising results, more studies on the subject are needed to help understand pain in patients with FM.